THE EFFECT OF FUNDAMENTAL FACTORS ON THE SHARE PRICES AT MINING COMPANIES LISTED ON THE IDX - Danang, Surya; Nofal, Mohammad; Hatma, Ramli (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2025)
Share prices on sectoral indices listed on the Indonesia Stock Exchange (IDX) shows that the mining sector experienced a decline in price in 2019 and then moved up in 2020, and increased significantly in 2021 and 2022. The purpose of this study was to determine the factors fundamentals that affect mining stock prices for the 2018-2022 period. This type of research was verification research with a population of all mining sector companies listed on the Indonesia Stock Exchange in 2018-2022, namely 57 companies. However, there were only 37 mining sub-sector companies that met the requirements as research samples. The data used is secondary data from the company's financial statements published on the Indonesian Stock Exchange's website. The data analysis technique used was panel data regression using the Eviews application version 12. The results of this study indicate that 1) ROE has a positive and significant effect on mining stock prices; 2) EPS has a positive and significant effect on mining stock prices; 3) CR has a positive and significant effect on mining stock prices; and 4) DER has a negative and significant effect on mining stock prices